2005
DOI: 10.1039/b510532c
|View full text |Cite
|
Sign up to set email alerts
|

Strain induced photoluminescence from silicon and germanium nanowire arrays

Abstract: The optical properties of silicon and germanium nanowires grown within the pores of hexagonal mesoporous silica matrices have been characterised by ultraviolet absorption and photoluminescence (PL) spectroscopy. A clear blue-shift in the PL of the semiconductor composite materials was observed as the diameter of the nanowires decreased from 85 to 22 A ˚.Powder X-ray diffraction revealed that, as the diameter of the confined nanowires decreased, the strain on the crystallographic structure of the nanowires incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 39 publications
(43 reference statements)
1
55
0
1
Order By: Relevance
“…Theoretically, researchers found that the band gap of Ge nanowires are dependent on several factors, such as size, [19][20][21] crystalline orientation, [20][21][22] surface chemistry, 22,23 and doping. 22,24 However, there is only very limited study 11 of strain effects on electronic properties of Ge nanowires.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, researchers found that the band gap of Ge nanowires are dependent on several factors, such as size, [19][20][21] crystalline orientation, [20][21][22] surface chemistry, 22,23 and doping. 22,24 However, there is only very limited study 11 of strain effects on electronic properties of Ge nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been observed, for example, in photoluminescence (PL) studies, and found to exhibit substantial blue-shift of emission with reduction of nanowire diameter. For instance, Audoit et al, 11 have grown Ge nanowires in the size range of 22 Å -85 Å using supercritical fluid methods. They observed a clear blue-shift in the PL of the nanowires compared to the Ge band gap of 0.66 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10] Other studies have mainly concerned visible PL from Ge nanocrystals embedded in various oxide matrices, and the role of the defects at the nanocrystal/ matrix interface or in the matrix itself. [11][12][13][14][15][16] In the case of Ge NWs, there are few reports of PL detected for band-to-band transitions in such nanowires, 17 due to the difficulty of detecting emission from unpassivated Ge NWs, which results from carrier trapping and nonradiative recombination. Among these, coherently strained Ge core/ SiGe shell nanowires exhibiting strong and bulk-like bandedge PL have been reported recently.…”
mentioning
confidence: 99%
“…Ez arra utal, hogy más folyamatok is befolyásolják a ZPL csúcshelyzetét. Egy lehetséges magyarázat lehet a kvantum pöttyöknél és kvantum gödröknél, valamint nanohuzaloknál megfigyelt tilos sáv kiszélesedés, ami ezen anyagok szerkezeti sajátosságaival áll kapcsolatban [60,61]. A nanoméret miatt ezen szerkezetek optikai tulajdonságai érzékenyebbek a szerkezeti hibákra, melyek torzíthatják a sávhatárokat.…”
Section: áBra: a Siv Centrum Spektrális Tulajdonságainak Meghatározásunclassified